Prevalencia de brucella canis en Perros Domesticos en el Barrio Salache, Provincia de Cotopaxi. - Santamaría Tenesaca, Francis Carlos (2018)
The project reseach is focused on investigating the presence of Brucella canis infection, by detecting antibodies in dogs from at-risk populations in the Salache neighborhood, Latacunga Canton, Cotopaxi province, which mainly come from serological studies with specific antigens which will be obtained from varied results depending on the province and origin of the animals. Canine Brucellosis is present throughout the world, being its total prevalence, resulting in 11% of contagion of the universes studied worldwide and being also a source of direct infection to man because it is considered a zoonotic disease that is seen reflected with reproductive problems in that who suffer from it. The data collected in this study of canine brucellosis prevalence come from serological studies, being reflected depending on the place and the sector that has carried out this research, obtaining a favorable result that initiates a total control of this pathology in domestic canines and its owners.